DISCRETE CHAIN MARKOV MODEL FOR MANAGING WATER DISCHARGE AND QUALITY IN CITARUM CASCADE RESERVOIR, JAWA BARAT, INDONESIA - wulandari, Suci
The guarantee of sustainable availability of clean water (water security) in Indonesia is now very worrying. This can be seen from the increasing scarcity of clean water (quality, quantity and continuity) to support life. This issue of water security then gave rise to the concept of integrated water resources management from upstream to downstream as a single system managed by one large manager to minimize conflicts that might arise. One of the main and priority watersheds because it is strategic in Indonesia is the Citarum watershed. The Citarum watershed is the main watershed in West Java which has a high critical land area and is strategic because apart from being a buffer for the capital city of Jakarta, the Citarum watershed is also the biggest supporter of food security and energy security in Indonesia. The Citarum watershed has 3 very large artificial pond areas (reservoirs) with various uses and operating in series which will then influence management efforts therein. With the largest population in West Java, the Citarum watershed has a very large pollutant load, resulting in a decrease in water quality. The water resources management model in the Citarum Cascade Reservoir with the main focus in the Nanjung area to the Jatiluhur Reservoir Outlet was then carried out regarding the quantity and quality aspects. In terms of quantity, this research discusses optimizing reservoir management and in terms of quality, this research discusses efforts to control pollution based on the condition of the reservoir stock volume in the worst year/dry year. Determination of the reservoir guidance trajectory is carried out based on the principle of mass balance. Classification of years is carried out using the discrete Markov method with 3 classes into dry, normal and wet conditions and based on Discrete Markov 5 classes into very dry, dry, normal, wet and very wet conditions. In efforts to optimize reservoir management, it was found that the correlation value using the Markov method showed an R value > 0.6 for various years. The increasing correlation value with the less historical data used shows that there is a change in the hydrological regime which causes the discharge value to change each period following changes in climate and land around the local watershed of the reservoir. Simulation of optimal reservoirs in the Citarum Cascade proves that optimizing the operational pattern of the Citarum Cascade Reservoir as an integrated management unit from upstream to downstream is proven if each reservoir is treated as a unique hydrological sub and is a function of space and time. Reference data on reservoir stock volume and reservoir physical parameters used later in pollution control efforts refers to the dry year (R5)/very dry year (R10) pattern which in this study appears to be the minimum with the worst conditions in 2011 where drought occurred almost throughout part of the Citarum watershed. To research aspects of water quality management, especially in stagnant water bodies. The eutrophication process then becomes the key so that determining T-P, T-N and BOD which are nutrient waste becomes the main parameters studied. Inventory and identification of potential pollutant loads in each Citarum Cascade Reservoir Catchment Area is carried out using the emission factor method. Based on the research results, it was found that the largest potential T-P and T-N pollutant loads in the Citarum Cascade Reservoir catchment area came from fisheries waste from Floating Net Cages, and for BOD the largest potential came from domestic waste (Saguling Reservoir) and fisheries waste (Cirata and Jatiluhur Reservoirs). When the source of the pollutant load has been inventoried and its magnitude identified, then a mass balance model simulation of the three key parameters in each reservoir is carried out using the one box model. From this method, results were obtained where the three water quality parameters studied could only reduce the concentration load in the water body if the pollutant load from upstream was reduced. The three reservoirs no longer have the capacity to accommodate the existing pollutant load, whether in dry, normal or wet years. The lack of capacity to carry pollutant loads means that the three reservoirs do not have the capacity to support the activities of living creatures in them. Because of this, the maximum load of pollutants in waters can be determined according to the standard water designation (quality standard class 3 or 2) in dry years (R5 In this research, a simple simulation was also carried out using a dynamic system with the help of Powersim to be able to see the efficiency and effectiveness of the solutions offered in order to reduce the pollutant load in each sector. The adaptive management process then begins with initial actions that have a reasonable chance of success. Future actions should be based on ongoing monitoring of the water body to determine how it responds to the actions taken. If you want to restore a watershed, then all life in that watershed must follow the laws, potential and limitations that exist within that watershed. All sectors of life in the watershed must follow the natural laws of the watershed so that sustainable development then becomes a development effort carried out by humans based on the laws, potential and limitations of the watershed in the area used/utilized